2010
DOI: 10.1002/hyp.7677
|View full text |Cite
|
Sign up to set email alerts
|

Generality of fractal 1/f scaling in catchment tracer time series, and its implications for catchment travel time distributions

Abstract: Abstract:Catchment travel time distributions reflect how precipitation from different storms is stored and mixed as it is transported to the stream. Catchment travel time distributions can be described by the mean travel time and the shape of the distribution around the mean. Whereas mean travel times have been quantified in a range of catchment studies, only rarely has the shape of the distribution been estimated. The shape of the distribution affects both the short-term and long-term catchment response to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
196
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(207 citation statements)
references
References 32 publications
(25 reference statements)
11
196
0
Order By: Relevance
“…As stated by Soulsby et al (2010) gamma distributions with α < 1 are most suitable to represent non-linear processes. Similarly several other studies found α values significantly smaller than 1 (McGuire et al, 2005;Hrachowitz et al, 2009Hrachowitz et al, , 2010Godsey et al, 2010;Kirchner et al, 2010;Speed et al, 2010;Birkel et al, 2012;Heidbüchel et al, 2012;Muñoz-Villers and McDonnell, 2012). On the other hand, our results reported that when coarse temporal resolutions were used (monthly or bi-monthly), the value of α approached 1, which could lead to erroneous deductions.…”
Section: Comparison Of Distribution Functionssupporting
confidence: 65%
See 1 more Smart Citation
“…As stated by Soulsby et al (2010) gamma distributions with α < 1 are most suitable to represent non-linear processes. Similarly several other studies found α values significantly smaller than 1 (McGuire et al, 2005;Hrachowitz et al, 2009Hrachowitz et al, , 2010Godsey et al, 2010;Kirchner et al, 2010;Speed et al, 2010;Birkel et al, 2012;Heidbüchel et al, 2012;Muñoz-Villers and McDonnell, 2012). On the other hand, our results reported that when coarse temporal resolutions were used (monthly or bi-monthly), the value of α approached 1, which could lead to erroneous deductions.…”
Section: Comparison Of Distribution Functionssupporting
confidence: 65%
“…Previous research accounted the groundwater contribution in 85 % of the total runoff, characterized by MTTs on the order of 2 to 4 years (Timbe et al, 2014;Crespo et al, 2012). A detailed description of the physical, hydro- logical and land cover characteristics of the catchment and main tributaries are given in Timbe et al (2014), whereas additional information on the climate and ecosystem gradients of the research area can be found in Bendix et al (2008), Fiedler and Beck (2008) and Wilcke et al (2008).…”
Section: Study Areamentioning
confidence: 99%
“…The issue has long been disregarded by hydrologists dealing with the quantification of input/output water fluxes, and has now rightfully become a cornerstone of hydrochemical studies. Typical applications include both atmospheric compounds entering the catchment through precipitation [Shaw et al, 2008;Godsey et al, 2010] or anthropogenic compounds injected onto the catchment, for example, due to farming activities [e.g., Basu et al, 2010;Rouxel et al, 2011;Kennedy et al, 2012]. Chlorides are an example of solutes which can be considered either geogenic or anthropogenic, because the mass input to the terrestrial part of the hydrologic cycle, whose proper quantification is sometimes problematic [Neal et al, 1988;Tetzlaff et al, 2007;Dunn and Bacon, 2008], originates either from atmospheric deposition and/or from the application of inorganic fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…[18] The gamma distribution [Kirchner et al, 2000;Godsey et al, 2010] with shape parameter (dimensionless) and scale parameter (¼ mTT/) [T]:…”
mentioning
confidence: 99%